University Philosophy Course: Reboot is Required - M. D. Shchelkunov (Высшее образование в России)
The philosophical training of tertiary-level students is designed to perform a number of functions assigned to it by society and the state. However, in recent years, it is no longer in demand by the majority of the educational process participants, since the university philosophy does not respond well to modern challenges from education, primarily to the need of digitalization and competence approach implementation. To preserve the disciplinary status of philosophy, the lecturers have to modernize the content, methods and forms of implementation of the discipline in order to increase its attractiveness in students’ minds, as well as the demand by society and the state. One of the possible ways to update the training course of philosophy is seen in its reorientation towards the development of students’ universal competencies prescribed in the state educational standards. In this case, the philosophical content becomes a tool to achieve this goal, and the philosophical heritage is used as a theoretical basis for mastering the technologies of mental action. The article presents the experience of Kazan University, where the philosophy course has recently become a tool for “system and critical thinking” competence training. Although a digital format of philosophical training has a number of cognitive advantages, nevertheless it is fraught with the risk that the philosophical value potential will not be fully realized. This risk can be minimized through a mixed format of teaching philosophy. Тo increase the demand for philosophy in higher education, the author offers a number of ways to enhance the role and importance of philosophy in students’ minds.